If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (-3) = 7 x + -3 = 7 Reorder the terms: -3 + x = 7 Solving -3 + x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 7 + 3 Combine like terms: -3 + 3 = 0 0 + x = 7 + 3 x = 7 + 3 Combine like terms: 7 + 3 = 10 x = 10 Simplifying x = 10
| 4x+6=12-10x | | 5b+10b=9 | | 5(b-1)=25 | | -6.4=6 | | 135=10x+65 | | 4x(10+6)= | | 2(4-9)+10= | | 40x+51=40x+46 | | 5x-20y=10 | | 2(4-9)+-10= | | 8n+4=8n-24 | | y=4c-3(c+2) | | 7w+5y=-13 | | 2(4-9)= | | 11+3p=5 | | 2(1+-4x)+3=45 | | 11n+2=35 | | -6(x+4)=23 | | x-24=12 | | -5y+11=31y | | 7-(5-8x)=4x+3x | | 2y-7=-12y-6 | | 3x+10y=25 | | 3x^2-17=-130 | | -39=-6x+3(x+4) | | 3x-6+2x=18 | | (2x-10)+(2x-20)=90 | | -3x-8=-x+2 | | 8(-b-4)=-88 | | 3x-47=-2 | | 6=-3(x+2)+5x | | 0.25a=4.0 |